Zundiqondisise!: investigating voice, visibility and agency in the work of Xhosa women crafters who work in community art centres in the Eastern Cape - Tutani, Zodwa (Rhodes University, Faculty of Humanities, Department of Fine Art, 2020)
A curatorial practice, Zundiqondisise! Reclaiming Our Voice is a twofold study comprised of curatorial practice and a written thesis, both of which are interdependent, examining the significance of space, agency, voice, and visibility in the works of Xhosa women crafters from the Eastern Cape. The study explores ways of reading and displaying indigenous art, as well as the archiving and inserting of these essential but neglected creative works of black women into the discourse of South African contemporary visual arts. This scholarship takes into account the social, cultural, and labour conditions that give rise to the perceived voicelessness in the 'craft' work of Xhosa women who work from community art centres. Through collaborating with two groups of women from two Eastern Cape art centres, namely Gompo Community Art Centre in East London and Nomzamo Old Age Centre in Ilitha Township, the study undertakes to locate, highlight and authorise these women's voices and agency. This undertaking is carried out through a textual inquiry and curated exhibition, two interdependent components of this study, working with black feminist and postcolonial theories that enable me to formulate a critical discourse and practice towards a reflective scholarship on black women's 'craft' work. It is a scholarship whose various chapters and curatorial interventions are tailored to excavate ancient Xhosa wisdom found in folklore and cultural practices of the everyday. This scholarship also provides new understandings that demonstrate and appreciate the fertile and significant though marginalised indigenous ways of creative expressions and knowledge production.
Keywords: Art centers -- Eastern Cape; Community arts projects -- Eastern Cape; Women artists, Black -- Eastern Cape; Ethnic art -- Eastern Cape; Agent (Philosophy); Art and society -- Eastern Cape; Voice (Philosophy); Critical discourse analysis; Postcolonialism and the arts; Feminism and art; Curatorship -- Eastern Cape; Art, Xhosa -- Conservation and restoration; Gompo Community Art Centre; Nomzamo Old Age Centre